Wilsonian Statecraft: Theory and Practice of Liberal Internationalism During World War I (America in the Modern World) - Ambrosius, Lloyd E. (Rowman & Littlefield Publishers, 1991)
To find more information about Rowman and Littlefield titles, please visit www.rowmanlittlefield.com.